Assessing the Effectiveness of Compliance Programs Through the Use of the Metaverse and Blockchain - Passas, Nikos; Coppola, Fabio (International Journal of Criminology and Sociology, 2025)
This paper examines how blockchain technology and the Metaverse can address persistent challenges in corporate compliance, with a focus on mitigating criminogenic asymmetries—such as regulatory arbitrage and opacity in cross-border transactions—through decentralized, transparent solutions. By contrasting the U.S. and Italian legal frameworks, we highlight the limitations of retrospective compliance evaluations and propose blockchain-enabled innovations, including immutable audit trails, smart contracts for automated enforcement, and Decentralized Autonomous Organizations (DAOs) to decentralize governance and embed compliance into protocol design. The Metaverse offers a simulated environment for stress-testing compliance protocols against emerging risks, while criminological theories (e.g., global anomie, legal-illegal interfaces) contextualize regulatory gaps in digital economies. We argue that DAOs, as digital-native entities, could revolutionize compliance by replacing hierarchical oversight with algorithmic governance, though challenges like jurisdictional fragmentation and identity verification persist. The study underscores the need for adaptive regulatory frameworks to harness these technologies while balancing transparency, accountability, and privacy.